Airborne occupational exposures and risk of oesophageal and cardia adenocarcinoma. Issue 2 (18th January 2006) - Jansson, C; Plato, N; Johansson, A L V; Nyrén, O; Lagergren, J
Abstract : Background: The reasons for the increasing incidence of and strong male predominance in patients with oesophageal and cardia adenocarcinoma remain unclear. The authors hypothesised that airborne occupational exposures in male dominated industries might contribute. Methods: In a nationwide Swedish population based case control study, 189 and 262 cases of oesophageal and cardia adenocarcinoma respectively, 167 cases of oesophageal squamous cell carcinoma, and 820 frequency matched controls underwent personal interviews. Based on each study participant's lifetime occupational history the authors assessed cumulative airborne occupational exposure for 10 agents, analysed individually and combined, by a deterministic additive model including probability, frequency, and intensity. Furthermore, occupations and industries of longest duration were analysed. Relative risks were estimated by odds ratios (OR), with 95% confidence intervals (CI), using conditional logistic regression, adjusted for potential confounders. Results: Tendencies of positive associations were found between high exposure to pesticides and risk of oesophageal (OR 2.3 (95% CI 0.9 to 5.7)) and cardia adenocarcinoma (OR 2.1 (95% CI 1.0 to 4.6)). Among workers highly exposed to particular agents, a tendency of an increased risk of oesophageal squamous cell carcinoma was found. There was a twofold increased risk of oesophageal squamous cell carcinoma among concrete and construction workers (OR 2.2 (95% CI 1.1 to 4.2)) and a nearly fourfold increased risk of cardia adenocarcinoma among workers within the motor vehicle industry (OR 3.9 (95% CI 1.5 to 10.4)). An increased risk of oesophageal squamous cell carcinoma (OR 3.9 (95% CI 1.2 to 12.5)), and a tendency of an increased risk of cardia adenocarcinoma (OR 2.8 (95% CI 0.9 to 8.5)), were identified among hotel and restaurant workers. Conclusions: Specific airborne occupational exposures do not seem to be of major importance in the aetiology of oesophageal or cardia adenocarcinoma and are unlikely to contribute to the increasing incidence or the male predominance.